LEPStr: A database for Mycobacterium leprae short tandem repeats. (2020) - Mohanty, Partha Sarathi; Saikia, Dimple; Kalra, Siddhant; Naaz, Farah; Bansal, Avi Kumar; Pawar, Harpreet Singh; Mohanty, Keshar Kunja; Sharma, Sandeep; Singh, Manjula; Patil, Shripad A.
Abstract: Short tandem repeats are short arrays of nucleotide sequences, and they have vital roles in many biological processes, including modulation of transcription, enhancement of gene expression, adaptation to a particular environment, and link to autosomal recessive diseases. Short tandem repeats are also used to study DNA fingerprinting for conservation genetics, taxon specific identification of species, infectious disease transmission dynamics, and marker assisted selection. In the present study we developed an online database viz ., LEPStr, for short tandem repeat of Mycobacterium leprae, along with copy number variation, gene of occurrence, and primers to amplify the tandem repeat regions. The whole genome sequence of M. leprae, MRHRU-235, accession no CP029543, was used as the template for screening of STRs with the tandem repeat finder. A layout of the database of LEPStr was developed using JavaScript (JS) and Java Server Pages (JSP) and implemented in MySQL database. A user-friendly interactive and free-to-use web interface was developed to browse Minisatellites and Microsatellites of M. leprae, along with primers to amplify the repeat regions. The LEPStr is an online database which is embedded with all short tandem repeats of M. leprae . LEPStr would be helpful in the typing of M. leprae strains, tracing the transmission dynamics of leprosy. Highlights: Short tandem repeats (STRs) are not junk bunch of DNA, but rather play a positive role in adaptive evolution. Historically, STRs are utilized to study DNA fingerprinting for conservation genetics, taxon specific identification of species, infectious disease transmission dynamics, and marker assisted selection. We screened the whole genome of Mycobacterium leprae, and a total of 166 STRs were detected. A user-friendly interactive and free-to-use web interface (LEPStr) was developed to browse Minisatellites and Microsatellites of M. leprae along with primers to amplify the repeat regions. LEPStr would be helpful in typing of M. leprae strains, tracing transmission dynamics of leprosy.